Immunohistochemical Features of Fibrillary Proteins at the Dermal-Epidermal Junction in Sepsis - Demyashkin, Grigory; Pogasyan, David; Silakov, Kirill; Pyatigorskaya, Nathalia; Borovaya, Tatyana; Ignatko, Irina; Morozova, Olga; Rostovskaya, Vera; Tsomartova, Dibakhan; Shidlovskii, Yulii; Mirontsev, Artem; Tarasov, Vadim; et al. (Scripta Medica, 2025)
Background/Aim. Sepsis is a life-threatening condition that significantly disrupts skin function and healing, yet the underlying mechanisms remain poorly understood. This study aimed to assess the fibrous components of the epidermal-dermal junction (Integrin-β1, laminin-332 and type IV collagen) in sepsis patients to better understand the structural changes in the skin during this condition. Methods. The study included 55 patients with sepsis (Group I) and a control group (Group II) of 10 deceased patients without infectious diseases. Patients’ medical records were analysed, including clinical data, disease duration, pharmacological therapy and comorbidities. Skin biopsies were processed for histological and immunohistochemical examination to assess the expression levels of laminin-332, type IV collagen and integrin-β1. Statistical analysis was performed using SPSS 12, with p-values ≤ 0.05 considered statistically significant. Results. Histological and immunohistochemical analyses revealed significant decreases in the expression of laminin-332, type IV collagen and integrin-β1 in sepsis patients (Group I) compared to the control group (Group II). These changes were more pronounced in older patients, indicating a correlation between age and the extent of disruption. The decrease in expression of these proteins suggests partial fragmentation of the basement membrane, leading to increased permeability, impaired epidermal-dermal attachment and disruption of regenerative processes. Conclusion. The observed changes in the fibrous components of the basement membrane, particularly the reduction in integrin-β1 expression, highlight the skin’s active role in the pathological process of sepsis. The impaired regenerative potential of the skin exacerbates its structural defects, hindering reparative processes and contributing to the progression of systemic inflammation. Pathological skin changes in sepsis are more pronounced in older individuals, likely due to the reduced activity of adaptive and compensatory mechanisms. Future research should focus on the recovery dynamics of these proteins and the potential for molecular-genetic analysis in understanding the long-term effects of sepsis on skin regeneration